DAMPAK PENGGUNAAN RUANG TERHADAP KUALITAS LINGKUNGAN KASUS DI WILAYAH PROPINSI LAMPUNG - Nandang Najmulmunir (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2002)
Lampung province has Basic Development Policy on Sustainable Development in the period of 1994/1995 - 1998/1999. The priority of development was focused on economic development policy. This policy have impacted to the change of land use and cover of land. Such changes have contributed to the environmental quality, especially in the regional environmental quality in particular the environmental stability.